Methylation Microarray Studies Highlight PDGFA Expression as a Factor in Biliary Atresia - Cofer, Zenobia C. (PLoS One, 2016)
Biliary atresia (BA) is a progressive fibro-inflammatory disorder that is the leading indication for liver transplantation in children. Although there is evidence implicating genetic, infectious, environmental, and inflammatory causes, the etiology of BA remains unknown. We have recently reported that cholangiocytes from BA patients showed decreased DNA methylation relative to disease- and non-disease controls, supporting a potential role for DNA hypomethylation in BA etiopathogenesis. In the current study, we examined the methylation status of specific genes in human BA livers using methylation microarray technology. We found global DNA hypomethylation in BA samples as compared to disease- and non-disease controls at specific genetic loci. Hedgehog pathway members, SHH and GLI2, known to be upregulated in BA, were both hypomethylated, validating this approach as an investigative tool. Another region near the PDGFA locus was the most significantly hypomethylated in BA, suggesting potential aberrant expression. Validation assays confirmed increased transcriptional and protein expression of PDGFA in BA livers. We also show that PDGF-A protein is specifically localized to cholangiocytes in human liver samples. Injection of PDGF-AA protein dimer into zebrafish larvae caused biliary developmental and functional defects. In addition, activation of the Hedgehog pathway caused increased expression of PDGF-A in zebrafish larvae, providing a previously unrecognized link between PDGF and the Hedgehog pathway. Our findings implicate DNA hypomethylation as a specific factor in mediating overexpression of genes associated with BA and identify PDGF as a new candidate in BA pathogenesis.